2009
DOI: 10.2503/jjshs1.78.273
|View full text |Cite
|
Sign up to set email alerts
|

Gum Accumulation of Japanese Apricot Fruit (Prunus mume Sieb. et Zucc.) was Expedited by Jasmonate

Abstract: Investigations were made into the effects of ethylene and jasmonate on gum formation of Japanese apricot fruit (Prunus mume Sieb. et Zucc.). We treated 'Benisashi' and 'Nanko' fruit that had been artificially wounded with a stainless steel needle and examined the relation between the formation of ethylene and gum accumulation. In addition, we treated 'Benisashi' fruit with ethephon, 1-methylcyclopropene (1-MCP), methyl jasmonate (JA-Me), ibuprofen, and aminoethoxyvinylglycine (AVG) to investigate the relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, ethylene and methyl jasmonate as plant hormones stimulate physiological activities in trees and promote their own functions, without critical disorder, resulting in more beneficial use than sulfuric acid. Some previous studies have demonstrated the induction of gum duct formation and gum exudation in broad-leaved trees using methyl jasmonate and ethylene as stimulants (Boothby 1983;Morrison et al 1987;Saniewski et al 2004;Matsumoto et al 2009). However, experiments involving the chemical induction of Rasamala balsam are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, ethylene and methyl jasmonate as plant hormones stimulate physiological activities in trees and promote their own functions, without critical disorder, resulting in more beneficial use than sulfuric acid. Some previous studies have demonstrated the induction of gum duct formation and gum exudation in broad-leaved trees using methyl jasmonate and ethylene as stimulants (Boothby 1983;Morrison et al 1987;Saniewski et al 2004;Matsumoto et al 2009). However, experiments involving the chemical induction of Rasamala balsam are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The upper-half cut of the fruit was immersed in 1% of hydrochloric acid in a desiccator attached to a vacuum pump and the internal air was collected by the water substitute method (Matsumoto et al, 2009). Ethylene was measured by injecting 1 mL of the collected gas into a gas chromatograph (G-3500;…”
Section: Fruit Quality Measurementmentioning
confidence: 99%